Combinação entre espécie fitorremediadora e carvão vegetal ativado em ambientes com a presença de herbicida persistente - Arthur, Clarissa (Universidade Federal de São Carlos, 2025)
The herbicide atrazine (ATZ) is widely used in agriculture for weed control; however, its toxicity and persistence in the environment have raised environmental concerns. ATZ inhibits photosynthesis in weeds, causing significant reductions in growth and enzymatic activity. Phytoremediation is a sustainable technique that uses plants to remove soil pollutants and emerges as a promising solution to address contamination from agricultural pollutants. In this context, Canavalia ensiformis (L.) DC. is a native Brazilian species that has been little studied regarding its phytoremediation potential, although it has been reported as an accumulator of organic and inorganic pollutants. Furthermore, recent studies indicate that the use of activated charcoal (biochar), produced from the pyrolysis of biomass, can enhance the remediation of contaminated soils due to its capacity for water and nutrient retention and adsorption of organic and inorganic pollutants. In this monograph, our hypothesis tested whether the use of eucalyptus-derived activated biochar, when combined with the plant species C. ensiformis, would exhibit a synergistic effect in its phytoremediation role of soils contaminated with atrazine. A generalized linear model (GLM) was used to analyze plant growth parameters, while the non-parametric Kruskal-Wallis test and Dunn's test were employed for the analysis of dry matter and enzymatic activity. The structure of this work includes a brief review with justifications for the topic, followed by the presentation of results in the format of a scientific manuscript, according to the standards of journals in the field. The results of this study provide relevant contributions to the potential application of biochar (BCH) in mitigating herbicide-induced stress in native Brazilian plants, reducing the phytotoxic effects of ATZ, and proposing strategies for the detoxification of contaminated soils, thereby supporting more sustainable agricultural practices.
Synergistic mitigation of atrazine-induced stress in Canavalia ensiformis using biochar for phytoremediation of contaminated soil
Keywords: Atrazina; Biochar; Canavalia ensiformis; Fitorremediação; Herbicida; Atrazine; Phytoremediation; Herbicide; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL; 2. Fome Zero e Agricultura Sustentável; 15. Vida Terrestre